CUMULATIVE DIETARY CARIOGENICITY AND DENTAL CARIES IN ADULTS. - Melekoğlu, Ebru; Yılmaz, Şehnaz İşci (Karya Journal of Health Science, 2023)
Objective: This study was conducted to determine the total cariogenic load of diet and its effect on dental caries in adults. Method: Patients aged 19-65 years (n=506) who applied for dental treatment were included in the study. A questionnaire including sociodemographic characteristics, a food consumption frequency questionnaire, and a decayed, missing, filled teeth (DMFT) index calculation were used to collect the data. The data were evaluated using SPSS (Statistical Package for Social Sciences) and Jamovi 2.3 package program and the level of significance was accepted as p<0.05. Mann Whitney U, Kruskal Wallis H, One-Way ANOVA, Spearman Correlation, Linear Regression, and Mediator Analysis tests were used to analyze the data. Results: In our study, the DMFT index score increased with increasing age, and the total cariogenic diet score increased as the education level decreased. There was a weak statistically significant positive correlation between the DMFT index scores and the total cariogenic diet score. It has been shown that an increase of 1 unit in the total cariogenic diet score causes an increase of 0.011 units in the DMFT index. In addition, it was found that the cariogenic diet had a positive mediator effect of 3.91% on the DMFT index. Conclusion: It is important to determine the cariogenic properties of the diet and to reduce the total cariogenic load of the diet in preventing dental caries and protecting oral and dental health in adults. For this reason, it may be more beneficial to evaluate the diet as a holistic and develop nutritional recommendations to reduce the risk of caries.